The Principal’s Strategy in Preparing Students Ready to Face the Industrial Revolution 4.0 - Nova Maryanti; Rohana Rohana; Muhammad Kristiawan (Universitas Bengkulu, 2020)
In this qualitative paper, we investigated in-depth about the strategy of the principal in preparing the students ready for the industrial revolution 4.0. The objects of research were State Vocational School 2 Palembang, State Vocational School 6 Palembang, Vocational School 2 Muara Enim, State Vocational School 1 Gelumbang, and Vocational School YTK Kimia Palembang. The data were carried out by interview, observation, and documentation. We found that some strategies used by 5 (five) Vocational Schools in South Sumatra in aligning education with the demands of the Industrial Revolution 4.0 era were improving the quality of facilities and infrastructure based on industrial needs (link and match). They upgraded teachers' competence appropriate with the era of industrial revolution 4.0 and then created competent and ready graduates in harmony with the program Making Indonesia 4.0 launched by the Ministry of Industry.